The Influence of Hedonic Motives, Browsing, and E-Payment on Impulsive Buying of Fashion Products in E-Commerce - Hellyani, Catharina Aprilia; Adriana, Erica; Andrena, Kanaya Meidy (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the effect of hedonic motives, browsing activities, and the use of e-payment on impulsive buying behavior of fashion products in e-commerce. Internet access and e-payment methods facilitate online shopping and encourage impulse buying, especially among Generation Z and Millennial who are often tempted by attractive promotions and satisfying browsing experiences. The research process was conducted through a survey involving respondents who use e-commerce platforms in Indonesia. The implementation method used was regression analysis to identify the relationship between the variables under study. The results show that hedonic motives and browsing activity have a significant influence on impulsive buying, while e-payment also contributes positively, accelerating the buying process. The implication of these findings is the importance of marketing strategies that pay attention to emotional factors and ease of transactions to increase sales of fashion products online.